2009
DOI: 10.1007/s00246-009-9384-7
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Vasospasm in an Adolescent Resulting from Marijuana Use

Abstract: This report is the first to describe coronary vasospasm, diagnosed by cardiac magnetic resonance imaging in an adolescent, resulting from marijuana abuse. A previously healthy 17-year-old male patient with severe chest pain, electrocardiographic changes, and urine test positive for cannabis, was diagnosed of having transient myocardial ischemia. The patient was discharged home and at this writing remains asymptomatic with a follow-up echocardiogram after 1 month showing normal left ventricular systolic functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
1
21
0
1
Order By: Relevance
“…In-vitro studies have shown that cannabis may have procoagulant effects, through increased expression of glycoprotein 11b-111a and P-selectin on platelets 6. Vasospasm may also occur, similar to cocaine use 7. Several case reports have documented MI triggered by marijuana use.…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro studies have shown that cannabis may have procoagulant effects, through increased expression of glycoprotein 11b-111a and P-selectin on platelets 6. Vasospasm may also occur, similar to cocaine use 7. Several case reports have documented MI triggered by marijuana use.…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana has various effects, such as vasoconstriction or vasodilation on different vascular beds and, may also cause coronary vasospasm or slow coronary flow (SCF) by its sympathetic or minimal pressor effects, especially in patients with atherosclerotic lesions present 2)4)9)12)15-17). Karabulut and Cakmak12) reported a case of inferior MI in a patient who had consumed marijuana regularly over a long period and whose coronary angiography demonstrated SCF.…”
Section: Discussionmentioning
confidence: 99%
“…Vakamızda akut MI'ın koroner trombüs ihtimalinin yanında koroner spazm nedeni ile de oluşmuş olabileceği kanısındayız. Daha önce mariuana kullanımına bağlı koroner vazospazm geliştiği magnetik rezonans ile gösterilmiştir [7]. Koroner vazospazma bağlı ventriküler anevrizma gelişmesi sık rastlanılan bir durum değildir, bu yönüyle de vakamız ayrı bir özellik arz etmektedir.…”
Section: Discussionunclassified